Can we use the CHA2DS2VASc score in Atrial Flutter?. (24th May 2021) - Brito, J; Rodigues, T; Nunes-Ferreira, A; Silverio Antonio, P; Couto Pereira, S; Valente Silva, B; Alves Da Silva, P; Barreiros, C; Lima Da Silva, G; Carpinteiro, L; Cortez-Dias, N; J Pinto, F; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: CHA2DS2VASc score is a well stablished prognostic score in atrial fibrillation population. However, considering patients with isolated atrial flutter no prognostic score are defined, regarding the embolic risk of this population. Purpose: To evaluate the capacity of CHA2DS2VASc score to predict cardiovascular death and major adverse cardiovascular events (MACE) in flutter patients (pts). Methods: Single-center retrospective study of pts submitted to CTA between 2015 and 2019, comprising two groups: I – pts with lone AFL; II – patients with AFL and prior AF. Clinical records were analyzed to determine the occurrence of MACE during the long-term follow up, defined as death (of cardiovascular or unknown cause), stroke, clinically relevant bleed or hospitalization due to heart failure or arrhythmic events. CHA2DS2VASc score was categorized into 3 groups: 0-1; 2-3; >4. Kaplan Meier survival curves were used to estimate the risk of events and the groups were compared using uni- and multivariate Cox regression analyses. Results: A total of 476 pts (66 ± 12 years, 80% males) underwent CTA: group I – 284 pts (60%), II – 192 pts (40%). Baseline characteristics were similar between groups, except for age with group I pts being older (68 ± 12, 64 ± 11, p < 0.01). The mean baseline CHA2DS2VASc was 2.3 ± 1.5 and the median post-CTA follow-up was 2.8 year. Considering global population, CHA2DS2VASc score was an independent predictor of cardiovascular death (OR: 1.49 95%CI 1.09-1.79, p = 0.08) and was a predictor of MACE even after adjustment for the diagnose of prior AF (OR 1.88, 95% IC 1.094-3.249, p = 0.022). Considering only the pts in group I CHA2DS2VASc score was a predictor of MACE (OR 3.03, 95% CI 1.112-8.278, p = 0.03) after adjustment for sex and age. Regarding the different MACE components, the score was a predictor of stroke (OR 4.45, IC 1.66-13.39, p = 0.04). In flutter pts CHA2DS2VASc score did not predict cardiovascular death. Conclusions:  In our population CHA2DS2VASc score was able to predict MACE events and stroke in patients with isolated atrial flutter. This suggests that in the future CHA2DS2VASc score could be applied to establish embolic risk in atrial flutter.